Seroprevalence and associated risk factors of Toxoplasma gondii infection in stray cats in Algiers urban area, Algeria - MOHAMED-CHERIF, A.; BENFODIL, K.; ANSEL, S.; AIT-OUDHIA, K.H. (Journal of the Hellenic Veterinary Medical Society, 2020)
Toxoplasmosis is a zoonotic parasitic disease caused by the protozoan Toxoplasma gondii. Human infections are common and generally asymptomatic, but they can become very dangerous in immunosuppressed and HIV-positive patients. The infection can also be serious if it is transmitted to the fetus during pregnancy. Infection in untreated mothers can lead to abortion, birth defects and blindness of the fetus. The aim of this study is to determinethe seroprevalence of Toxoplasma IgT antibodies in cats in the urban area of Algiers. From December 2017 to August 2018, blood samples from 184 stray cats were collected and analyzed for IgG antibodies against T. gondii using an ELISA method. Overall, the prevalence of T. gondii infection in stray cats was 58.15% (107/184). There was no statistically significant difference between male and female cats. The rate of seropositivity of T. gondii increased with age (p <0.05). There was no statistically significant difference between the different regions from which the samples were taken. The results of the present study showed the high seroprevalence of toxoplasmosis in Algiers rather than in other countries. Due to the high seroprevalence of Toxoplasma IgG antibodies in cats, it is recommended to include in the prenatal evaluation, together with the adoption of a screening test and the determination of the IgG antibody titer in the high-risk populations (young girls, pregnant women) public information programs on the disease and measures that can contribute to prevention